Peningkatan Produktivitas Usaha Pemotongan Ayam Menggunakan Poultry Depilator Machine di Desa Jenangger Batang-Batang sumenep - Hafni, Romaiki; Asrori , Moh. Fijri; M. Halimi (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2022)
This research aims (1) to analyze the production activities of the Chicken Slaughter Business in Jenangger Village, Batang-Batang District, Sumenep Regency, (2) to analyze the Increase in Productivity of Chicken Slaughter Business Using Poultry Depilator Machine in Jenangger Village, Batang-Batang District, Sumenep Regency. This research is a field research with a qualitative-descriptive approach. The techniques used in data collection are observation, interviews and documentation. The data analysis technique is descriptive-analysis which is concluding data reduction, data display, and conclution/verification. The results of this research are: First, production activities in the chicken slaughter business in Jenangger Village, Batang-Batang District, Sumenep Regency are divided into several stages, namely: the stage of chicken health checks and manual slaughter in accordance with Islamic rules, the stage of soaking chickens in hot water, the stage of removing chicken feathers using Poultry Depilator Machine which is continued then continued using manual technique for maximum results, and the marketing stage. Second, the use of Poultry Depilator Machine in chicken slaughter business in Jenangger Village, Batang-Batang District, Sumenep Regency can increase business productivity compared to before using the machine. This is proven by the increase in the amount of production which is increasing from a daily average of 60 chickens to 200 chickens per day, and the time required for daily production is more efficient which is decreasing from 7 hours to 5 hours. However, the use of the Poultry Depilator Machine does not completely replace the manual technique of removing chicken feathers, because in fact, after the removal using the machine, it still requires removal using manual technique to get maximum results. Keywords: The Increase, Productivity, Poultry Depilator Machine.